METHODOLOGICAL APPROACHES TO THE DEVELOPMENT OF COMMUNICATIVE CULTURE OF FUTURE EDUCATORS OF PRE-SCHOOL EDUCATION IN THE MAGISTRACY - Kharkivska, Aryna (Mountain School of Ukrainian Carpaty, 2019)
Based on the analysis of scientific-pedagogical and special literature, the author substantiates the essence of the concept of "communicative culture of the future preschool teacher". It is proved that for the development of communicative culture of future preschool teachers in the conditions of magistracy it is expedient to use the following methodological approaches. The child-centered approach focuses the educational process on the development of the communicative culture of future preschool educators, which provides the conditions for the development of cognitive interest of students in the world of preschool childhood, motives for pedagogical interaction and understanding with children, valuable human interaction who has certain rights to be recognized by future caregivers; professionals who are able to penetrate the world of feelings and emotions, ready to accept the views of children, showing confidence, respect and tolerance. Taking into account the systematic approach allows analyzing the process of development of communicative culture of future preschool teachers, but does not provide knowledge on the basis of which principles it is necessary to build the educational process, what content, forms and methods to fill it. The value of the andragogical approach is that it implies the need to determine the content, forms and methods of development of communicative culture of future educators in the conditions of magistracy, which largely correspond to adult learning, encourage critically to assess the level of their professional knowledge, skills, skills, promote the development of its culture. Taking into account the activity approach as a theoretical and methodological basis for the study of the development of communicative culture of future preschool educators is determined by the fact that it allows to determine the components of the system of development of communicative culture of future teachers, their procedural regularity, enables such organization of the process of development of communicative education, involves constant communication between teachers and students. The use of the linguo-didactic approach as a theoretical and methodological basis for the study of the development of communicative culture of future preschool educators directs the study to take into account the system-forming position of language as a general personality trait that determines the spiritual, intellectual, linguistic development of a future educator. The cultural approach directs the educational process to the development of the communicative culture of future preschool educators, which provides the creation of conditions for the formation and development of communicative personality of future educators, able to build subject-subject relationships, optimally use the means of communication according to age-psychologists and individuals features of the interlocutor, follow the etiquette rules in communication, as well as capable of cultural self-development and successful professional self realization in professional activity.